Penggunaan Artificial Intelligence (AI) di Kalangan Mahasiswa PAI dan Implikasinya terhadap Kemampuan Berpikir Kritis - Nisrina Nisrina; Kurnia Rahma Ramadani; Sutrisna Sutrisna (STIKes Ibnu Sina Ajibarang, 2026)
Artificial Intelligence (AI) has increasingly influenced higher education, including learning practices among students of Islamic Education (PAI). Applications such as ChatGPT, Claude AI, and Gemini are widely used to support academic activities, including information searching, understanding course materials, idea generation, and assignment completion. This study aims to examine the use of AI among PAI students and analyze its implications for critical thinking skills. A qualitative descriptive approach was employed at the Islamic Education Program of UIN Salatiga. Data were collected through written interviews with 12 students selected using purposive sampling and analyzed using an interactive data analysis model. The findings reveal that AI has become an important part of students’ academic activities due to its perceived usefulness and ease of use. Most participants demonstrated critical thinking behaviors by verifying AI-generated information, comparing multiple academic sources, and evaluating the accuracy of responses before using them for academic purposes. Nevertheless, excessive dependence on AI was found to potentially reduce students’ independent learning and analytical engagement. The study concludes that AI has a dual impact on critical thinking: it can enhance critical thinking when used reflectively and responsibly, but it may also weaken cognitive involvement when relied upon excessively. Therefore, strengthening AI literacy, digital literacy, and critical thinking skills is essential in higher education learning practices.